Analisis Kegiatan Kolase untuk Menstimulus Perkembangan Motorik Halus Anak Difabel di RA Ar-Rafif Tirtomartani Kalasan, Yogyakarta - Majidah S., Khotimatul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Analysis of collage activities to stimulate fine motor skills of children with disabilities, the purpose of this study was to analyze how far this collage activity was to stimulate fine motor skills of children with disabilities, this study was conducted on group B children in Ra Ar-Rafif tirtomartani Kalasan Yogyakarta, with 13 normal children , 2 of them are children with disabilities accompanied by accompanying medical therapy, the type of research used is qualitative research that produces descriptive data written or oral from the required subject and observable behavior. So, qualitative research should not isolate individuals or organizations into variables or research hypotheses, but the authors are considered to be intact instruments. The results of this study can be seen from the concept of the teacher teaching this collage activity with efforts to guide and direct each child including the disabled child, with the guidance and guidance, children can collect birds using rice material well and neatly, but the level of neatness and achievement is different in every child, so there are 6 people who have neat categories, and 7 children including children who have not been trained as out of the pattern of birds that are given, the presence of black marks from glue material, but the children with disabilities are a little neat because of the guidance specifically, it can be said that this collage activity can stimulate the fine motor skills of a disabled child